Simulation of the Krafla Geothermal Field - Jonsson, V. (Lawrence Berkeley Laboratory, 1978)
Simulation studies have recently been made of the Krafla Geothermal Field in Northern Iceland. The field is close to boiling in the formation at depths of 1800 meters and below. Two simulations were undertaken. The first studied radial flow, i.e., behavior around a production well. It was found that the relative permeability distribution of the liquid and vapor phase had very little effect on the general results. The simulation shows that while the well produced superheated steam after a few days of production, the superheated front moved only 1/10 the distance of the boiling front, which extended to a radial distance of over 200 meters after one-half year production. The second simulation investigated the two-zone system which is believed to exist in Krafla. This study simulated one well producing 50 kg/s from both zones for a period of 33 years. It showed that boiling in the formation begins near the production well and at the connection between the two zones. After 20 years, boiling takes place in the entire lower zone region with saturation (steam volume fraction) ranging from 0-30 percent. After 33 years, saturation increased to over 60 percent at the top of the lower zone, just under the caprock separating the two zones. Higher production rates will augment the spread of the saturation proportionately to the ratio of mass production.